Healthcare resource utilization trends in patients with acute myeloid leukemia ineligible for intensive chemotherapy receiving first‐line systemic treatment or best supportive care: A multicenter international study. (13th April 2022) - Ito, Tomoki; Sanford, David; Tomuleasa, Ciprian; Hsiao, Hui‐Hua; Olivera, Leonardo José Enciso; Enjeti, Anoop Kumar; Conca, Alberto Gimenez; del Castillo, Teresa Bernal; Girshova, Larisa; Martelli, Maria Paola; Guvenc, Birol; Bui, Cat N.; et al.
Abstract: Objectives: This retrospective chart review examined real‐world healthcare resource utilization (HRU) in patients with AML ineligible for intensive therapy who received first‐line systemic therapy or best supportive care (BSC). Methods: Data were collected anonymously on patients with AML who initiated first‐line hypomethylating agents (HMA), low‐dose cytarabine (LDAC), other systemic therapy, or BSC. HRU endpoints included hospitalizations, outpatient consultations, transfusions, and supportive care. Results: Of 1762 patients included, 46% received HMA, 11% received LDAC, 17% received other systemic therapy, 26% received BSC; median treatment durations were 118, 35, 33, and 57 days, respectively. Most patients were hospitalized, most commonly for treatment administration, transfusion, or infection (HMA 82%, LDAC 93%, other systemic therapy 83%, BSC 83%). A median number of hospitalizations were 2–6 across systemic groups and two for BSC, with median durations of 8–18 days. Transfusion rates and outpatient consultations were highest for HMA (80% and 79%) versus LDAC (57% and 53%), other systemic therapy (57% and 63%), and BSC (71% and 66%). Antivirals/antibiotics and antifungals were used more frequently than growth factors (72–92%, 34–63%, and 7–27%, respectively). Conclusion: Patients with AML ineligible for intensive therapy have high HRU; novel therapies are needed to alleviate this burden.